Serum lipoprotein (a) concentrations are inversely associated with T2D, prediabetes, and insulin resistance in a middle-aged and elderly Chinese population - Ding, Lin (J Lipid Res, 2015)
Lipoprotein (a) [Lp(a)], an LDL-like particle, has been proposed as a causal risk factor for CVD among general populations. Meanwhile, both serum Lp(a) and diabetes increase the risk of CVD. However, the relationship between serum Lp(a) and T2D is poorly characterized, especially in the Asian population. Therefore, we conducted a cross-sectional study in 10,122 participants aged 40 years or older in Jiading District, Shanghai, China. Our study found that the prevalence of T2D was decreased from 20.9% to 15.0% from the lowest quartile to the highest quartile of serum Lp(a) concentrations (P for trend <0.0001). Logistic regression analyses showed that the odds ratios and 95% confidence intervals of prevalent T2D for quartiles 2–4 versus quartile 1 were 0.86 (0.73–1.01), 0.88 (0.75–1.04), and 0.76 (0.64–0.90) (P for trend = 0.0002), after adjustment for traditional confounding factors. Moreover, the risks for prevalent prediabetes, insulin resistance, and hyperinsulinemia were also decreased from the lowest to the top quartile. This inverse association between serum Lp(a) and T2D was not appreciably changed after we adjusted hypoglycemic medications or excluded the subjects with hypoglycemic and/or lipid-lowering agents and/or a history of self-reported CVD.